BACK ON CIRCE'S ISLAND. (December 2020) - van Veldhuizen, Michiel
Abstract : The reception of Circe's island in and through Classical Antiquity has largely focused on the enigmatic sorceress herself. The long literary chain of interpretive topoi —Circe the witch, the whore, the temptress—stretches from Apollonius, Virgil, Ovid, and Dio Chrysostom to Spenser, Calderón, Joyce, Margaret Atwood, and Madeline Miller. Her role as Odysseus' benefactor, so unmistakable in Homer, is soon forgotten; to Virgil, she is above all dea saeva, ('the savage goddess', Aen. 7.19). One distinguishing feature of Circe and her reception is the focus on representation: the enchantment of Circe, as Greta Hawes puts it, is above all a study in allegory. From the moment Circe put a spell on Odysseus' companions, transforming them into animals in Book 10 of the Odyssey, Circe has invited analogical reasoning, centered on what the transformation from one being into another represents. More often than not, this transformation is interpreted according to a dualist thinking about humans and animals: subjects are transformed from one being into another being, thus representing some moral or physical degradation. This article, by contrast, concentrates on Circe's island through the lens of becoming-animal, the concept developed by Gilles Deleuze and Félix Guattari in the tenth plateau of A Thousand Plateaus, '1730: Becoming-Intense, Becoming-Animal, Becoming-Imperceptible…'. I explicate the concept of becoming-animal by applying it to a Deleuzian encounter with Circe's island, both in its ancient articulations and in its various receptions, including H.G. Wells's science fiction novel The Island of Dr. Moreau .